Mechanical joinability of microstructurally graded structural components manufactured from hypoeutectic aluminium casting alloys - Neuser Moritz; Schlichter Malte Christian; Hoyer Kay-Peter; Bobbert Mathias; Meschut Gerson; Schaper Mirko (MATEC Web of Conferences)
Lightweight design is a driving concept in modern automotive engineering to minimize resource consumption over a vehicle's lifecycle through multi-material design, which relies on the use of joining techniques in car body fabrication. Multi-material design and the increasing trend towards producing large structural components using the megacasting process pose considerable challenges, particularly in the mechanical joining of aluminium-silicon (AlSi) castings. These castings typically exhibit low ductility and are prone to cracking when mechanically joined. Based on the excellent castability of hypoeutectic AlSi alloys, these are applied in sand casting and die casting as well as in megacasting. With a silicon content between 7 wt% and 12 wt%, these AlSi-alloys have a plate-like silicon phase that initiates cracks during mechanical joining. To enhance the joinability of castings, the research hypothesis is that improved solidification conditions enable a significant modification in the microstructure and therefore, increase the mechanical properties. During the manufacture of the castings using the sand casting process, the solidification conditions within the structural elements are varied to modify the microstructure to obtain castings with graded microstructure. The castings are evaluated using mechanical, microstructural and joining testing methods and finally, a microstructure-joinability correlation is established.